2021
DOI: 10.7759/cureus.14363
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lactulose vs. Polyethylene Glycol for Bowel Preparation in Colonoscopy: A Randomized Controlled Study

Abstract: BackgroundColonoscopy is the method of choice to evaluate colonic mucosa and the distal ileum, allowing the diagnosis and treatment of many diseases. Appropriate bowel preparation necessitates the use of laxative medications, preferentially by oral administration. These include polyethylene glycol (PEG), sodium picosulfate, and sodium phosphate (NaP). Lactulose, a semi-synthetic derivative of lactose, undergoes fermentation, acidifying the gut environment, stimulates intestinal motility, and increases osmotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The findings demonstrate that, in comparison with the PEG-alone control group, the combination can decrease patients’ pain and water intake while also improving the quality of bowel preparation. In an another study conducted by Jagdeep et al ( 30 ) in 2021, lactulose is a significantly more palatable form of bowel preparation with good bowel cleansing comparable with PEG, causing minor discomforts without causing any hemodynamic changes; Li et al ( 6 ) also reached the same conclusion, and the detection rate of intestinal lesions in the lactulose group was higher than that in the PEG group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 81%
“…The findings demonstrate that, in comparison with the PEG-alone control group, the combination can decrease patients’ pain and water intake while also improving the quality of bowel preparation. In an another study conducted by Jagdeep et al ( 30 ) in 2021, lactulose is a significantly more palatable form of bowel preparation with good bowel cleansing comparable with PEG, causing minor discomforts without causing any hemodynamic changes; Li et al ( 6 ) also reached the same conclusion, and the detection rate of intestinal lesions in the lactulose group was higher than that in the PEG group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 81%
“…The literature screening process is shown in Figure 1. Characteristics of the included literature 11 RCT articles were included, of which 9 were Chinese articles [7][8][9][10][11][12][13][14][15], 2 were English articles [16,17], and the publication time was between 2013 and 2021. The study country was mainly China, laxative of choice for the experimental group was lactulose, and the intervention of choice of the control group were mainly polyethylene glycol electrolyte and oral magnesium sulfate.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In terms of random allocation: 8 out of 11 included studies stated that the random allocation method was used [8, 10-14, 16, 17], the other 3 did not state their allocation method [7,9,15], with 4 of the studies [10][11][12][13] not explicitly stating their choice of random allocation method. 4 studies [8,14,16,17]specified that they used the random number table method; among them, the research by Li [16] and Jagdeep [17] have the highest quality, having used the single-blind method within the group, with a low risk of bias; the rest of the literature was not blinded; and the selective reporting of trial results and other risk indicators of bias were not reported in the literature due to their uniqueness, however, the overall quality of the literature is moderate. The methodological quality of the literature is shown in Figure 2.…”
Section: Methodological Quality Assessment Of the Included Literaturementioning
confidence: 99%
“… 6 Recently, some studies have adopted lactulose as an intestinal cleanser, which exhibited a positive effect. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%